Հայոց Արևելից կողմանց վարչաքաղաքական կացությունը 5-13-րդ դարերում (համառոտ ակնարկ) - Հովսեփյան, Վոլոդյա («ԱՐՑԱԽ» հրատ.)
Սույն հոդվածի նպատակն է ցույց տալ, որ պատմական Մեծ Հայքի թագավորության Արևելից կողմանց միջնադարյան վարչաքաղաքական կացության ուսումնասիրությունը ոչ միայն գիտական, այլև քաղաքական նշանակություն ունի, քանզի Ադրբեջանի պատմագրությունը, քաղաքական նկատառումներով նենգափոխում է հայ ժողովրդի պատմությունը՝ կասկածի տակ դնելով հայկական պետականությունն անգամ։ Եվ դա այն դեպքում, երբ մեր օրերում, Ադրբեջանի ղեկավարությունը ոչ միայն Արցախի, այլև Հայաստանի Հանրապետության տարածքը լկտիությամբ ադրբեջանական է համարում։ Ուսումնասիրության խնդիրներից են՝ 1. Նոր հիմնավորումներով ճշգրտել Աղվանից թագավորության վերացման, մարզպանության ստեղծման, Հայաստանից պոկված Արցախ և Ուտիք գավառների՝ Աղվանքին միացման ժամանակի հետ կապված հարցերը։ 2. Հայոց Արևելից կողմանց վարչաքաղաքական կարգավիճակն Աղվանից մարզպանության կազմում։ 3. Աղվանից մարզպանության վերացումից հետո ձևավորված տեղական հայկական իշխանական տների կացությունը IX-XIII դարերում։ Աշխատանքի ընթացքում կիրառվել են մի շարք հատուկ մեթոդներ, մասնավորապես՝ կառուցվածքային, պատմա-իրավական, համակարգային, վերլուծականև այլն։ Աշխատանքում հիմնավորել ենք, որ Մեծ Հայքի թագավորության վերացումից հետո նրա արևելյան նահանգները՝ Արցախն ու Ուտիքը, հայտնվելով մեկ այլ վարչաքաղաքական միավորի՝ Աղվանքի կազմում, մնացին զուտ հայկական, ինչը հիմք հանդիսացավ հայկական պետականության հետագա շարունակականության՝ Համամ Արևելցու թագավորության, Փառիսոսի և Խաչենի իշխանությունների, Խամսայի մելիքությունների Լեռնային Ղարաբաղի ինքնավար մարզի, 1991-2023 թվականներին՝ Լեռնային Ղարաբաղի (Արցախի) Հանրապետության կարգավիճակներով։ The purpose of this article is to demonstrate that studying the medieval administrative and political landscape of the eastern provinces of Greater Armenia holds not only scholarly but also political importance. This is particularly relevant given that Azerbaijani historiography, driven by political motives, distorts the history of the Armenian people and even questions the existence of Armenian statehood. This occurs against the backdrop of contemporary Azerbaijani leadership openly laying claims not only to Artsakh but also to the territory of the Republic of Armenia. The objectives of the research are: 1. to interpret the issues related to the abolition of the kingdom of Aghvan, the establishment of the marzpanate and the time of accession of the provinces of Artsakh and Utik, which separated from Armenia, to Aghvan using new substantiations. 2. to determine the administrative and political status of the eastern provinces of Armenia within the Aghvan province. 3. to present the situation of the local Armenian princely houses after the abolition of the marzpanate of Aghvan in the IX-XIII centuries. In the course of the work we applied a number of special methods, namely: structural, historical-legal, systematic, analytical, etc. We have substantiated that after the abolition of the marzpanate of Aghvan in the IX-XIII cc. The purpose of this article is to demonstrate that studying the medieval administrative and political landscape of the eastern provinces of Greater Armenia holds not only scholarly but also political importance. This is particularly relevant given that Azerbaijani historiography, driven by political motives, distorts the history of the Armenian people and even questions the existence of Armenian statehood. This occurs against the backdrop of contemporary Azerbaijani leadership openly laying claims not only to Artsakh but also to the territory of the Republic of Armenia. The objectives of the research are: 1. to interpret the issues related to the abolition of the kingdom of Aghvan, the establishment of the marzpanate and the time of accession of the provinces of Artsakh and Utik, which separated from Armenia, to Aghvan using new substantiations. 2. to determine the administrative and political status of the eastern provinces of Armenia within the Aghvan province. 3. to present the situation of the local Armenian princely houses after the abolition of the marzpanate of Aghvan in the IX-XIII centuries. In the course of the work we applied a number of special methods, namely: structural, historical-legal, systematic, analytical, etc. We have substantiated that after the abolition of the marzpanate of Aghvan in the IX-XIII cc. Цель данной статьи — показать, что изучение средневекового административно-политического бытования восточных провинций исторического Великого Армянского царства имеет не только научное, но и политическое значение. Азербайджанская историография по политическим мотивам искажает историю армянского народа, ставя под сомнение сам факт существования армянской государственности. И это происходит в условиях, когда сегодня руководство Азербайджана считает азербайджанскими не только территорию Арцаха, но и территории Республики Армения. Основные задачи исследования: 1. с уточнёнными аргументами определить вопросы, связанные с ликвидацией Кавказской Албании, созданием марзпанства, временем присоединения к Кавказской Албании отколовшихся от Армении провинций Арцах и Утик. 2. административно-политический статус восточных провинций Армении в составе марзпанства Кавказской Албании. 3. положение армянских княжеских домов, сформировавшихся после ликвидации марзпанства Кавказской Албании, в IX-XIII веках. В процессе работы применены ряд специальных методов, в частности: структурный, историко-правовой, системный, аналитический и другие. В статье обосновывается, что после уничтожения Великого Армянского царства его восточные области — Арцах и Утик, — оказавшись в составе другого административно-политического образования, Кавказской Албании, остались чисто армянскими. Это стало основой для дальнейшего продолжения армянской государственности в форме царства Хамама Восточного, княжеств Парижана и Хачена, меликств Хамсы, автономной области Нагорного Карабаха, а с 1991 по 2023 год — Республики Нагорный Карабах (Арцах).
Keywords: Իրավագիտություն